Detection and quantification of protein phosphatase inhibitor-1 gene expression in total rat liver and isolated hepatocytes - Aleem, Eiman; Mayer, Doris; Bannasch, Peter (Molecular and cellular biochemistry, 2001)
The mRNA expression of protein phosphatase inhibitor-1 (inhibitor-1) in rat liver was demonstrated using highly sensitive semi-quantitative reverse transcription polymerase chain reaction (RT-PCR). Quantification by real-time RT-PCR (LightCycler technology) yielded the same copy number of inhibitor-1 mRNA in total rat liver and isolated hepatocytes (12 copies per cell). This novel finding shows that rat liver expresses indeed inhibitor-1 mRNA, albeit in low amounts. The low copy number explains why the mRNA had not been detected by Northern blotting so far. For comparison, about 425 copies/cell were detected in brain and 2500 copies/cell in skeletal muscle from rat. The full-length coding sequence of rat liver inhibitor-1 was cloned and sequenced, 100% homology with the muscle cDNA was obtained, indicating the expression of the same gene in liver and muscle. In vitro transcription and translation yielded a protein (Mr ~ 30 kDa) which could be detected with a specific antibody by immunoblotting. This indicates an intact open reading frame of inhibitor-1 in rat liver. Immunoblotting of liver extract yielded a very weak band which comigrated with the inhibitor-1 proteins from muscle and brain. It is concluded that mRNA expression of inhibitor-1 may have implications for the regulation of protein phosphatase-1 (PP1) in rat liver.